2
$\begingroup$

Evaluate the sum $\sum^{\infty}_{n=1} \frac{n^2}{6^n}$

My approach :

$= \frac{1}{6}+\frac{2^2}{6^2}+\frac{3^2}{6^3} +\cdots \infty$

Now how to solve this I am not getting any clue on this please help thanks.

$\endgroup$
4
$\begingroup$

Starting with \begin{align} \frac{1}{1-t} = \sum_{n=0}^{\infty} t^{n} \end{align} then differentiate and multiply by $t$ to obtain \begin{align} \frac{t}{(1-t)^{2}} = \sum_{n=0}^{\infty} n t^{n}. \end{align} Repeating leads to \begin{align} \sum_{n=0}^{\infty} n^{2} \ t^{n} = \frac{t(1+t)}{(1-t)^{3}}. \end{align} Now let $t = 1/6$ for which \begin{align} \sum_{n=0}^{\infty} \frac{n^{2}}{6^{n}} = \frac{42}{125}. \end{align}

$\endgroup$
  • 3
    $\begingroup$ Oh right, this is $Li_{-2}(6^{-1})$. Completely missed that. $\endgroup$ – Gina Jun 10 '14 at 4:08
0
$\begingroup$

Break $n^2$ into two parts: $\underbrace{n(n-1)} + \underbrace{{}\quad n\quad {}}$.

The first part appears in the second derivative of $x^n$ and the second part in the first derivative:

\begin{align} \sum_{n=1}^\infty n^2 x^n & = \sum_{n=1}^\infty x^2\Big(n(n-1) x^{n-2} \Big) + x\Big(nx^{n-1}\Big) \\[10pt] & = \left(x^2 \frac{d^2}{dx^2} \sum_{n=1}^\infty x^n\right) + \left( x\frac{d}{dx}\sum_{n=1}^\infty x^n \right) \\[10pt] & = \left( x^2 \frac{d^2}{dx^2} \frac{x}{1-x}\right) + \left( x\frac{d}{dx} \frac{x}{1-x} \right) \\[10pt] & = \cdots\cdots \end{align}

(Finally at the end, put $x=1/6$.)

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.